ڕۆڵی میدیای نوێ لە پێکهێنانی کاری هونەری شێوەکاری هاوچەرخ لە هەرێمی کوردستانی عێراق دا - سەعید, پ. د. ڕێبوار; عوێز, م. نەرمین مصطفى (Sulaimani Journal for Humanities, 2023)
New developments and changes have always had a significant impact on art, because art reflects its time. The problem of this research is to answer the question of whether the new developments and successive changes in technology and new media have played a role in the production of contemporary artwork in the Iraqi Kurdistan Region, for example, Sulaimani? what extent are new media reflected and influential within contemporary works of art? The aim of the study is to highlight the role of new media in the plastic arts at the presents, especially in the Iraqi Kurdistan Region (Sulaimani) as an example. The importance of this research is to work on the artworks that use new media as a medium in the production of their works in the field of contemporary plastic ar ts, as well as discovering and presenting the capabilities and characteristics of new art media in the Kurdistan Region. That is very important for art centers and art students in universities and colleges, Descriptive method of analysis has been used to conduct the study. The research community consists of works and artistic projects that use new media, which have a distinct set and a recent history and are available in detail after research and collection of works for this purpose, in Sulaimani from 2012 to 2022 and the sample of study is the same as the community is study, which was done through random sampling. The importance of this study is also highlighted on the role of new media as a medium and in the different ways of creating a contemporary art. As a result of this research, the researcher has reached several points, the most important of which is that new media is part of contemporary art in the Iraqi Kurdistan Region, Sulaimani for example.
Keywords: میدیای نوێ هاوچەرخ